Event-Triggered Adaptive Synchronous Control of Interconnected Microgrids Under Denial-of-Service Attacks - Xiaodan Li; Lei Zhang; Hongbin Liu; Xiaoyu Yi; Xiaochun Liu; Zichen Yi (IEEE Access)
Considering the threat of malicious Denial-of-Service (DoS) attacks in the communication network layer of distributed interconnected microgrids, which disrupt information exchange among subsystems and compromise synchronization control algorithms, an event-triggered secure synchronization control protocol is proposed for DC interconnected microgrids under DoS attacks. The proposed protocol ensures bus voltage regulation, current sharing among distributed generation units, and charge balance among distributed energy storage units. To reduce the communication burden on controllers, a fully distributed dynamic event-triggered communication mechanism is developed. This mechanism incorporates adaptive parameters to eliminate the dependence of event-triggering mechanism design on global information of the topology, and employs a dynamic event-triggering threshold, resulting in significantly lower triggering frequency compared to static methods. A switching-like control strategy is then applied to design a secure event-triggered synchronization control protocol resilient to DoS attacks. The stability of the closed-loop system is rigorously analyzed through the construction of a switching-like Lyapunov function. Additionally, Zeno behavior is ruled out through theoretical analysis. The effectiveness of the proposed protocol is validated via a simulation case study.